Experimental signatures of Kalb-Ramond-like particles - P. C. Malta; J. P. S. Melo; C. A. D. Zarro (Journal of High Energy Physics)
Abstract We analyse phenomenological signatures of Kalb-Ramond-like particles, described by an antisymmetric rank-2 tensor, when coupled to fermionic matter. The latter is modelled by a tensor current coupled directly to the Kalb-Ramond field or by a pseudovector current coupled to the rank-1 dual of the field-strength tensor. We obtain limits on the coupling constants to fermions and mass of the Kalb-Ramond-like particles by investigating their impact on the hyperfine splittings of hydrogen, the tree-level unitarity of the S matrix for e − + e + → ℓ − + ℓ + scattering with ℓ ≠ e and the differential cross section for Bhabha scattering. Assuming that the couplings to fermions are independent of the fermion species, the strongest 95%-CL bounds we find are from LEP data at s $$ \sqrt{s} $$ = 136.23 GeV, namely g PV/Λ ≲ 6.3 × 10−13 eV−1 and g T ≲ 1.3 × 10−12 (m/eV), both for m ≪ s $$ \sqrt{s} $$ (here Λ is a characteristic energy scale). These limits can be improved in upcoming lepton colliders due to enhanced precision, as well as higher energies.